The Effect of Breastfeeding Counseling on Increasing the Success of Exclusive Breastfeeding in Postpartum Mothers - Herlina, Herlina; Mustamin, Rini (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Exclusive breastfeeding for the first 6 months of life is a crucial step in reducing infant morbidity and mortality. However, the success rate of exclusive breastfeeding remains low due to mothers' lack of knowledge and skills in breastfeeding. Objective: To determine the effect of breastfeeding counseling on increasing the success of exclusive breastfeeding in postpartum mothers. Method: This study uses a quasi-experimental design with a pretest-posttest approach. control group. A sample of 60 postpartum mothers selected using purposive sampling technique was divided into an intervention group (breastfeeding counseling) and a control group (without counseling). The research instrument was a questionnaire on knowledge, attitudes, and observations of breastfeeding practices. Data analysis used paired t- test and independent t- test. Results: There was a significant difference between the intervention group and the control group in the success of exclusive breastfeeding (p < 0.05). Breastfeeding counseling improved mothers' knowledge, attitudes, and skills in breastfeeding, thus having a positive impact on the success of exclusive breastfeeding. Conclusion: Breastfeeding counseling had a significant effect on increasing the success of exclusive breastfeeding in postpartum mothers. Suggestion: Health workers need to routinely provide breastfeeding counseling to postpartum mothers to increase the coverage of exclusive breastfeeding.